Endothelial Glycocalyx Shedding Predicts Donor Organ Acceptability and Is Associated With Primary Graft Dysfunction in Lung Transplant Recipients. Issue 6 (June 2019) - Sladden, Timothy M.; Yerkovich, Stephanie; Grant, Michelle; Zhang, Fuming; Liu, Xinyue; Trotter, Michael; Hopkins, Peter; Linhardt, Robert J.; Chambers, Daniel C.
Abstract : Background: The endothelial glycocalyx, a sieve-like structure located on the luminal surface of all blood vessels, has been found to be integral to regulation of capillary permeability and mechanotransduction. Given this, we investigated the role of endothelial glycocalyx breakdown products in organ donors and recipients in terms of acceptability for transplant and risk of primary graft dysfunction (PGD). Methods: Endothelial glycocalyx breakdown products were measured in the peripheral blood of 135 intended and actual organ donors. Breakdown product levels were tested for association with donor demographic and clinical data, organ acceptability for transplant along with lung recipient outcomes (n = 35). Liquid chromatography mass spectrometry analysis was performed to confirm glycosaminoglycan levels and sulfation patterns on donor samples (n = 15). In transplant recipients (n = 50), levels were measured pretransplant and daily for 4 days posttransplant. Levels were correlated with PGD severity and intubation time. Results: Decreased hyaluronan levels in peripheral blood independently predicted organ acceptability in intended and actual donors (odds ratio, 0.96; [95% confidence interval, 0.93–0.99] P = 0.026). Furthermore, high donor syndecan-1 levels were associated with PGD in recipients (3142 [1575–4829] versus 6229 [4009–8093] pg/mL; P = 0.045). In recipient blood, levels of syndecan-1 were correlated with severe (grades 2–3) PGD at 72 hours posttransplant (5982 [3016–17191] versus 3060 [2005–4824] pg/mL; P = 0.01). Conclusions: Endothelial glycocalyx breakdown occurs in lung transplant donors and recipients and predicts organ acceptability and development of PGD. Glycocalyx breakdown products may be useful biomarkers in transplantation, and interventions to protect the glycocalyx could improve transplant outcomes. Abstract : Supplemental Digital Content is available in the text.